Developing strategy for rural transformation to alleviate poverty in Pakistan: Stylized facts from panel analysis - ABEDULLAH; Shujaat FAROOQ; Farah NAZ (Journal of Integrative Agriculture, 2023)
Sustainable income growth and poverty reduction remain critical challenges at the forefront of research in Pakistan, particularly in rural areas. To overcome these challenges, the role of rural transformation (RT) has emerged and gained importance in recent years. The present study is based on district-level data and covers the period from 1981 to 2019. The study attempts to quantify the role of rural transformation in boosting rural per capita income and alleviating rural poverty in the country. The study also aims to explore the impact of stages of rural transformation on rural per capita income and rural poverty alleviation. The empirical findings reveal that rural transformation (RT1 and RT2) is essential in enhancing rural per capita income and alleviating rural poverty. The role of the share of high-value crops (RT1) is more pronounced than the share of non-farm employment (RT2) in boosting rural per capita income and poverty alleviation. The trend of larger contribution of RT1 to enhance rural per capita income also continued at 2nd stage of rural transformation. In the case of poverty reduction, at 3rd stage of rural transformation, the role of RT2 is dominant. Our results indicate that districts at higher stages of rural transformation (both RT1 and RT2) tend to correlate positively with increased rural per capita income and reduced poverty rates, suggesting that progress in rural transformation is associated with improved economic conditions. However, it is important to note that this correlation does not necessarily imply a direct causal relationship between rural transformation and these economic outcomes; other factors may have influenced this relationship. In addition, the welfare impacts are more noticeable among the districts where a simultaneous shift from grain crops to cash crops and from farm employment to non-farm employment is observed. The study provides baseline information to learn experiences from fast-growing districts and to replicate the strategies in other districts, which boosts the RT process that may increase rural per capita income and enhance poverty reduction efforts.